2020
DOI: 10.1016/j.gene.2020.144892
|View full text |Cite
|
Sign up to set email alerts
|

Role of regulatory miRNAs of the Wnt/ β-catenin signaling pathway in tumorigenesis of breast cancer

Abstract: Breast cancer is the most commonly diagnosed malignancy in women worldwide.Recently, uncontrolled expression of microRNAs was detected in several human disorders like cardiovascular, neurological, intestinal and autoimmunity diseases. MicroRNAs (miRNAs) are now investigated as novel prognostic and diagnostic biomarkers for several solid tumors like breast, lung, and gastrointestinal cancers. Current data suggest that miRNAs are implicated in various oncogenic processes implicated in breast cancer carcinogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Accumulating evidence has shown that the Wnt/β-catenin pathway not only determines mammary development, but also regulates self-renewal, tumorigenesis and differentiation of CSCs in various cancers including breast cancer, lung cancer, and prostate cancer. β-catenin is the core target of this signaling, and its nuclear accumulation and translocation leads to transcription of downstream genes such as ABCG2 , HMGB1 , cyclin D1 , c-myc , and Axin2 , which are strongly correlated to cancer chemosensitivity ( Cheng et al, 2019 ; Rahmani et al, 2020 ; Yousefnia et al, 2020 ). Upon the activation of β-catenin, the complex composed of Axin and glycogen synthase kinase-3β (GSK-3β) prevents the phosphorylation and degradation of β-catenin, increases the concentration of β-catenin in cytoplasm, and then transfers into the nucleus to interact with T cell transcription factor/lymphoid enhancer factor to activate the Wnt1/β-catenin signal pathway, and finally start the transcription of downstream target genes such as cyclin D1 and c-myc , resulting in abnormal proliferation of CSCs and tumor drug resistance ( Maiese, 2014 ; Schuijers et al, 2014 ; Ashouri et al, 2016 ; Hassanian et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence has shown that the Wnt/β-catenin pathway not only determines mammary development, but also regulates self-renewal, tumorigenesis and differentiation of CSCs in various cancers including breast cancer, lung cancer, and prostate cancer. β-catenin is the core target of this signaling, and its nuclear accumulation and translocation leads to transcription of downstream genes such as ABCG2 , HMGB1 , cyclin D1 , c-myc , and Axin2 , which are strongly correlated to cancer chemosensitivity ( Cheng et al, 2019 ; Rahmani et al, 2020 ; Yousefnia et al, 2020 ). Upon the activation of β-catenin, the complex composed of Axin and glycogen synthase kinase-3β (GSK-3β) prevents the phosphorylation and degradation of β-catenin, increases the concentration of β-catenin in cytoplasm, and then transfers into the nucleus to interact with T cell transcription factor/lymphoid enhancer factor to activate the Wnt1/β-catenin signal pathway, and finally start the transcription of downstream target genes such as cyclin D1 and c-myc , resulting in abnormal proliferation of CSCs and tumor drug resistance ( Maiese, 2014 ; Schuijers et al, 2014 ; Ashouri et al, 2016 ; Hassanian et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Wnt/ β -catenin pathway has been reported to regulate tumorigenesis and progression of BC [ 31 33 ]. Li et al showed that TRIM63, a novel oncogene, promotes BC cell proliferation and migration via activating the Wnt/ β -catenin signaling pathway [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have been reported that upregulation of Wnt/β-catenin was shown to be one of the mechanisms to resist PI3k inhibitors. In addition, the use of β-catenin inhibitors sensitizes breast cancer cells to PI3K inhibitors [353].…”
Section: Mapk/erk Signaling Pathwaymentioning
confidence: 99%